PENGARUH PEMBERIAN IMUNOMODULATOR Echinacea purpurea (radix) TERHADAP TITER ANTIBODI AVIAN INFLUENZA (AI) DAN NEWCASTLE DISEASE (ND) PADA BROILER BETINA - Dahlia, Purnama Edy Santosa, Siswanto, dan Madi Hartono (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2019)
This research was intended to determine the level of antibody to AI and ND in female broilers given drinking water with the addition of E. purpurea (radix) at different doses. This research was conducted in December 2018-January 2019 in the Cage of an Integrated Field Laboratory, Faculty of Agriculture, Lampung University and antibody titer analysis carried out at the Hall Veterinary of Lampung. This research used completely randomized design (CRD) with four treatments and three repetition, drinking water without E. purpurea (radix) (control) (P0), drinking water with 3 mg / kg BW / day E. purpurea (radix) (P1), drinking water with 6 mg / kg BW / day E. purpurea (radix) (P2), and drinking water with 9 mg / kg BW / day E. purpurea (Radix) (P3). The results of this research showed that the AI antibody titer was not significantly different and had an antibody titer below the standard (not protective). Antibody titer of ND showed that all treatments were not significantly different, but the treatment of P3 had the highest antibody titer. Keywords: Immunomullatory, E. purpurea, Antibody titer, Avian influenza, Newcastle disease, Female broiler